Forensic footwear evidence - Bodziak, William J. (CRC series in practical aspects of criminal and forensic investigations., 2017)
The utilization of footwear impression evidence continues to evolve with new materials, equipment and techniques, providing an increased ability to detect, record, enhance, and examine this form of evidence. Recently developed technology now allows investigators to more efficiently or, in some cases, instantly link multiple crime scenes where impressions have been produced by the same perpetrator.